HIGH AND LOW ACHIEVERS’ SELF-REGULATION IN LEARNING ENGLISH (RETAIN, 2017)
HIGH AND LOW ACHIEVERS’ SELF-REGULATION IN LEARNING ENGLISH Miftha Safira Firmansyah English Department, Faculty of Languages and Arts, State University of Surabaya mifthafirmansyah@mhs.unesa.ac.id Ahmad Munir, Ph.D. English Department, Faculty of Languages and Arts, State University of Surabaya ahmadmunir@unesa.ac.id Abstrak Penelitian ini fokus pada regulasi diri siswa kelas sepuluh tingkat Sekolah Menengah Atas. Peneliti memilih 53 siswa yang terdiri dari 28 siswa dengan perolehan kemampuan tinggi dan 25 siswa dengan perolehan kemampuan rendah sebagai subjek penelitian ini. Penelitian ini dilakukan untuk mengetahui (1) tingkat regulasi diri siswa dengan perolehan kemampuan tinggi dan rendah, (2) tingkat regulasi diri siswa berdasarkan tujuh indikator regulasi diri, (3) dan hubungan regulasi diri siswa dengan perolehan kemampuan mereka dalam mempelajari Bahasa Inggris. Penelitian ini merupakan penelitian korelasi yang diolah secara kuantitatif. Instrumen yang digunakan dalam penelitian ini adalah nilai Bahasa Inggris yang diperoleh siswa di akhir semester dan kuesioner. Para subjek penelitian diberi angket yang berisi 21 pernyataan. Kuesioner tersebut menggunakan skala Likert untuk memudahkan peneliti dalam penghitungan skor yang diperoleh dari setiap siswa, guna menjawab pertanyaan penelitian pertama dan kedua. Pertanyaan penelitian terakhir dijawab menggunakan bantuan analisis Spearman di SPSS. Hasil penelitian menunjukkan bahwa sebagian besar anak dengan perolehan kemampuan tinggi (47%) berada pada tingkat regulasi diri yang tinggi juga, sedangkan sebagian besar anak dengan perolehan kemampuan rendah (60%) berada pada tingkat regulasi diri yang rendah pula. Hasil regulasi diri mereka juga berbeda-beda bila diuraikan berdasar pada tujuh indikator regulasi diri. Selanjutnya, hasil korelasi menunjukkan adanya hubungan yang positif antara regulasi diri dan kemampuan berbahasa Inggris siswa (r – 0.441) dengan  = 0.00 (p < 0.05). Kata Kunci: Siswa berkemampuan tinggi dan rendah, regulasi diri, indikator, hasil kemampuan. Abstract This study focused on tenth graders’ self-regulation in learning English. The aim of this study is to determine the students’ self regulation and the correlation between their self-regulation and their achievement in English. The researcher chose 53 tenth graders from a senior high school in Surabaya, which is consist of 28 high achievers and 25 low achievers. This study was conducted in order to find out (1) Do the high achievers and low achievers use strategies in regulating their English? If yes, how are their self regulations? (2) How is the self regulation level of high and low achievers based on each indicator of Self-Regulated Learning? (3) Is there any correlation between the students’ self regulation and their achievements in learning English? Moreover, this research belongs to correlational research. The researcher used students’ English score and questionnaire as instruments of this study. There were 21 statements in the questionnaire. The questionnaire used Likert Scale as a calculation scale to answer the first and second research questions. Furthermore, the last research question was done by Spearman’s Rank Order Correlation on SPSS. The result showed that most of high achievers (47%) are highly regulated, while low achievers (60%) are least regulated. The result also showed the different level of their self-regulation based on sseven indicators of self-regulated learning. In addition, the last result showed the positive correlation between self-regulation and the students’ achievements in learning English (r – 0.441) dengan α = 0.00 (p < 0.05). Keywords: high achiever, low achiever, self-regulated learning, indicator, achievement